Older persons’ views and experience of elder abuse in southwestern Nigeria: A community-based qualitative survey (2014)
Objectives: Conventionally, existing information on elder abuse has been institution based, professionally driven, and in high-income countries. This study addresses the prevailing gap in knowledge through direct consultation of older persons in the community about their perceptions of elder abuse. Method: Eight focus group discussions were carried out among males and females aged 60 years and above in a rural and an urban community in south western Nigeria. Data were transcribed and analyzed based on emergent themes. Results: Findings from the study show that the perception of abuse by the respondents included the standard typologies except sexual abuse as well as societal issues such as disrespect and lack of recognition. Discussion: Our study revealed a high level of awareness and experience of elder abuse among the participants in both communities. Effective social welfare and health services aided by targeted government policies are needed to improve the quality of life of the elderly.